Using the good lives model (GLM) in clinical practice: Lessons learned from international implementation projects. (March 2022) - Prescott, David S.; Willis, Gwenda M.
Abstract: Efforts to implement the Good Lives Model (GLM) in offending treatment programs highlight common challenges across diverse settings. Long described as an overarching framework for rehabilitation, the GLM has recently been reconstructed as a practice framework . In this paper, the authors explore how the reconstruction of the GLM as a practice framework can help address challenges to GLM implementation observed internationally. Challenges to effective implementation of the GLM in a variety of settings and across cultures are described, based upon the authors' experiences helping programs and practitioners use the GLM to their fullest potential. Drawing on the theoretical resources of practice frameworks, it offers ideas for how programs and practitioners can respond to these challenges as implementation efforts unfold. Specifically, the paper focuses on how core values and principles of the GLM (Level 1 of practice frameworks) can inform intervention guidelines (Level 3 of practice frameworks). Research has been clear that proper implementation of any treatment approach can take considerable time to conduct properly; it is the authors' hope to equip programs and practitioners with ideas for moving forward thoughtfully with the GLM.